Design and Build Planning for the Integration of LAN/WAN/WiFi Network Systems with Centralized Management and Network Monitoring System - Maulina, Riska; Kalistowen Bie; Excel Daud; Hardi Yanti (LPPM Universitas Sari Mulia, 2025)
This study discusses the design of the integration of LAN, WAN, and WiFi network systems with centralized management and the implementation of Network Monitoring System (NMS) in Building E of Sari Mulia University with an area of ±600 m². The initial state of the network that is still running separately, without clear segmentation and without real-time monitoring, leads to limited network visibility, connectivity disruptions, and uneven WiFi distribution. This study aims to design and develop an integrated network system that combines LAN, WAN, and WiFi infrastructures with centralized management and NMS to improve network performance, security, and management efficiency. The method used is the network design method which includes needs analysis, network architecture design, device implementation and configuration, and system performance testing. Network integration is carried out through the implementation of a managed switch-based backbone, Virtual Local Area Network (VLAN) segmentation, strengthening security using firewalls and VPNs, and continuous network monitoring using NMS. The design results show an increase in connection stability, network security, and infrastructure management efficiency, with a ≥99.5% uptime and even WiFi coverage throughout the building, so that this system design is considered feasible to be applied as an integrated network solution in the educational institution environment.